Extraction of crude gelatin from duck skin: effects of heating methods on gelatin yield - Kim, Tae-Kyung (Poult Sci, 2019)
The disposal of by-products of duck production, including duck skin, is a serious concern as it results in environmental pollution. The objectives of this study were to investigate the optimal pretreatment conditions for swelling duck skin and their extraction methods as a novel source. Gelatin was extracted using water bath, sonication, superheated steam, and microwave extraction methods. The gelatin extraction yield and gelatin powder yield were the highest with the superheated steam extraction method. The melting point and gel strength of gelatin extracted using the superheated steam method were the lowest. The viscosity of gelatin extracted with the superheated steam and microwave extraction methods was higher than that of gelatin extracted with the other methods. The sodium dodecyl sulfate-polyacrylamide gel electrophoresis patterns of gelatin extracted using the superheated steam and microwave extraction methods showed more intense bands than those of gelatin extracted using the other methods. Our results showed that gelatin extracted from duck skin using the superheated steam extraction method had optimal physical properties and therefore can be used in meat products.